2021
DOI: 10.2147/jpr.s323362
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of Radiofrequency Neurotomy in Chronic Low Back Pain: A Systematic Review and Meta-Analysis

Abstract: Purpose The objective of the systematic review and meta-analysis is to evaluate the efficacy of radiofrequency neurotomy as a therapeutic lumbar facet joint intervention. Patients and Methods Utilizing the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) checklist, a systematic review and meta-analysis was performed. A comprehensive literature search of multiple data sources from 1966 to September 2020 including manual searches of bibliography… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 86 publications
0
9
0
Order By: Relevance
“…A systematic review and meta-analysis were performed on the basis of methodological and reporting quality of systematic reviews as described by the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) [60,61]. Methodology from other reviews was also utilized [62,63].…”
Section: Methodsmentioning
confidence: 99%
“…A systematic review and meta-analysis were performed on the basis of methodological and reporting quality of systematic reviews as described by the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) [60,61]. Methodology from other reviews was also utilized [62,63].…”
Section: Methodsmentioning
confidence: 99%
“…Chen et al 128 demonstrated the effective application of radiofrequency neurotomy on facetogenic chronic LBP via a meta-analysis. Janapala et al 129 reported a systematic review and meta-analysis including 12 randomized controlled trials, and they found that the short-term and long-term efficacy of lumbar radiofrequency neurotomy were debated. Al-Najjim et al 130 conducted a systematic review including 4 studies with randomized controlled trials, which compared the outcome of radiofrequency denervation compared to sham or placebo procedures for the treatment of facetogenic LBP.…”
Section: Managementmentioning
confidence: 99%
“…Chen et al 128 demonstrated the effective application of radiofrequency neurotomy on facetogenic chronic LBP via a meta-analysis. Janapala et al 129 reported a systematic review and meta-analysis including 12 randomized controlled trials, and they found that the short-term and long-term efficacy of lumbar radiofrequency neurotomy were debated. Al-Najjim et al 130…”
Section: Medial Branch Radiofrequency Ablationmentioning
confidence: 99%
“…The transmission of nociceptive impulses is blocked by applying an electric current to coagulate the sensory nerves, which deactivates the nerves (2). A recent systematic review supported the superiority of conventional radiofrequency (CRF) over sham controls and other treatments in terms of short-term (≤6 months) and long-term (>6 months) improvement (5). However, there has been no systematic review of the effectiveness evaluation of other emerging RF denervation treatments, such as pulsed RF denervation, RF facet capsule denervation, and RF ablation under endoscopic guidance.…”
Section: Introductionmentioning
confidence: 99%